Role of structured rehabilitation protocol in post surgical cases of restricted mouth opening - Ankita Chugh; Kriti Mishra; Kushal K Sahu; Yogesh Mittal; Vinay K Chugh (Wolters Kluwer Medknow Publications, 2020)
Background: Long term effectiveness of surgical management of chronically restricted mouth opening in OSMF or TMJ ankylosis depends largely on postoperative physiotherapy. This in turn is dependent on patient's compliance. Use of adjunctive aids besides pharmacotherapy that reduces patients pain and improves compliance with exercise is warranted. Aims: To evaluate the role of TENS and structured rehabilitation programme in postoperative physiotherapy in OSMF and TMJ ankylosis patients. Methods and Materials: A pilot study was conducted in which 6 patients of restricted mouth opening were put on a structured rehabilitation protocol in which TENS, heat and cold therapy with structured mouth opening exercise regimes. Interincisal opening, VAS score and a subjective assessment of post surgical discomfort was evaluated. Results and Conclusions: Results revealed an improved compliance and cooperation by patients. Pain on VAS scale also reduced from mean of 7.8 on day 1 to 3.6 on day 5 in this group. The mean discomfort on day 3 was reported as mild to moderate. An early attainment of passive mouth opening closest to intraoperative mouth opening was also reported on day 5 which is usually not achievable without any physiotherapy intervention.